Memaknai Frasa “Menggenapkan Apa yang Kurang pada Penderitaan Kristus”: Studi Teks Kolose 1:24 - Baskoro, Paulus Kunto; Setiasih, Yemima (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2023)
Paul's statement in Colossians 1:24 is interesting to analyze. The words "completing what is lacking in the afflictions of Christ" present believers with some difficulties. At first, these words reveal indirectly that there is a lack in the sufferings of Christ, that the effectiveness of our Lord's sufferings is limited, and that the purpose of redemption must be completed or accomplished through Paul's sufferings. The sufferings of Christ are perfect, sufficient to atone for the sins of mankind, and do not need to be completed. What needs to be completed or fulfilled is suffering to preach the Gospel about Christ, who died and was raised, so that many will know Him and the power of His Resurrection. This research will be studied by the descriptive qualitative method. First, this study aims to provide a theological answer to the meaning of “fulfilling what is lacking in the sufferings of Christ.” Second, it is given an essential meaning for every believer to live more and more earnestly in Christ because of the perfect atonement that Jesus made. Abstrak Pernyataan Paulus dalam Kolose 1:24 menjadi hal yang menarik untuk di analisis. Perkataan "melengkapkan apa yang kurang dalam penderitaan Kristus” menghadapkan orang percaya pada beberapa diskusi Nas. Sepintas nampaknya perkataan ini mengungkapkan secara tidak langsung bahwa ada kekurangan dalam penderitaan Kristus, bahwa keefektifan penderitaan Kristus itu terbatas dan tujuan penebusan harus dilengkapi atau diselesaikan melalui penderitaan Paulus. Penderitaan Kristus sudah sempurna, sudah cukup untuk menebus dosa manusia dan tidak perlu digenapkan lagi. Hal yang perlu digenapkan atau dipenuhkan adalah penderitaan demi mengabarkan Injil, tentang Kristus yang berinkarnasi menjadi manusia, mati menjadi korban tebusan dan telah dibangkitkan dari antara orang mati. sehingga banyak orang akan mengenal Dia dan kuasa kebangkitan-Nya. Penelitian ini akan dikaji secara metode kualitatif deskritif. Tujuan dari penelitian ini adalah Pertama, memberikan jawaban teologis terhadap makna “menggenapkan apa yang kurang pada penderitaan Kristus.” Kedua, memberikan makna penting bagi setiap orang percaya untuk hidup makin lebih sungguh-sungguh dalam Kristus, karena penebusan yang sempurna yang dilakukan Yesus.